2002
DOI: 10.3168/jds.s0022-0302(02)74304-x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Clinical Lameness on the Milk Yield of Dairy Cows

Abstract: This paper investigates the impact of lameness on milk yield. The dataset includes approximately 8000 test-day milk yields from 900 cows on five farms in Gloucester, UK, collected over 18 mo from 1997 to 1999. The data were structured to account for repeated measures of test-day yield (1 to 10 per cow) and analyzed to account for this autocorrelation. Factors affecting milk yield included: farm of origin, stage of lactation, parity, and whether a cow ever became lame. In clinically lame cows, milk yield was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
350
12
27

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 435 publications
(421 citation statements)
references
References 19 publications
25
350
12
27
Order By: Relevance
“…In addition, it was found that if a cow had one or more mastitis cases in its previous lactation then it would produce 1.2 kg/day less milk over the whole of current lactation compared with a cow with no mastitis in its previous lactation. Green et al (2002) estimated that on average lame cows fail to produce ,350 kg of milk (with a range of 160 to 550 kg), and decreased milk yield occurred from 4 months before till 5 months after a cow was diagnosed as clinically lame.…”
Section: Genetic Correlationsmentioning
confidence: 99%
“…In addition, it was found that if a cow had one or more mastitis cases in its previous lactation then it would produce 1.2 kg/day less milk over the whole of current lactation compared with a cow with no mastitis in its previous lactation. Green et al (2002) estimated that on average lame cows fail to produce ,350 kg of milk (with a range of 160 to 550 kg), and decreased milk yield occurred from 4 months before till 5 months after a cow was diagnosed as clinically lame.…”
Section: Genetic Correlationsmentioning
confidence: 99%
“…Lameness, defined as a deviation in gait resulting from pain or discomfort from hoof or leg injuries and disease, can affect many cows (some studies have reported prevalence of up to 55%; Clarkson et al, 1996), reduces milk production, feed intake and fertility and is costly for producers (Green et al, 2002;O'Callaghan, 2002;Hernandez et al, 2005). Most gait evaluations assess changes relative to 'normal gait', but such changes can be difficult to judge; Whay et al (2003) reported that producers identified only one of every four cases of dairy cattle with hoof injuries or disease, and another study found that only one of every three cows were correctly identified (Espejo et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Bicalho et al [9] showed that lame cows produced 3.02±0.23 kg more milk prior to lameness in comparison with the control group. Using body fat reserves for milk production entails mobilizing fat from many tissues, including the digital cushion [8] . Other studies have also revealed a connection between a lower BCS and lameness [6,10,12,21] , as well as a connection between a higher BCS and a higher LS [22] .…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of lameness is complex and multifactorial. The factors influencing lameness include the following: housing conditions, social interactions/influence, stages of lactation, pregnancy or calving and high yielding [6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%